Solar based Smart Sanitizer Dispenser System with Internet of Things (IoT) Technology - Radhakrishnan, Venkateswaran; Al Murazza Ba Abood, Ahood Aqil Alawi Al Murazza Ba Abood; Rogelio Gutierrez, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In response to the growing demand for efficient and sustainable hygiene solutions, this project introduces a Solar-Powered Smart Sanitizer Dispenser System leveraging IoT technology. The system aims to address the need for touchless and accessible hand sanitization in various environments, including public spaces, healthcare facilities, and commercial establishments. By integrating solar power as the primary energy source, the system offers autonomy and eco-friendliness, reducing dependency on conventional electricity grids and minimizing environmental impact. The core components of the system include a smart dispenser unit equipped with sensors for detecting hand proximity, a reservoir for storing sanitizer solution, and a microcontroller unit responsible for data processing and IoT connectivity. Through the IoT interface, users can remotely monitor sanitizer levels, receive real-time usage statistics, and manage dispenser settings, enhancing operational efficiency and maintenance. Furthermore, the incorporation of solar panels ensures continuous operation even in off-grid locations, making the system suitable for deployment in remote or outdoor settings where access to electricity may be limited. Maximizing the efficacy of solar power conversion and extending operational uptime.
Keywords: Solar Power; Smart Sanitizer Dispenser; IoT Technology; Touchless Hygiene; Sustainability; Remote Monitoring; Energy Efficiency; Environmental Impact; Public Health; Renewable Energy Integration